Impacto de la Inmigración sobre el Crecimiento de la Renta Per Cápita de Ecuador (2001-2015) - Germán Zurita, Eduardo (2017)
The analysis of the effects of immigration on per capita income tends to increase the percentage of the working age population by fully integrating them into the productive system, which fosters economic growth and increases well-being in the population. The paper seeks to determine the Impact of Immigration on the growth of per capita income in Ecuador through the multiple linear regression model. This model is based on the theory of demographic transition, with the premise that immigrants are attracted by the wage differences of their country with respect to another. In conclusion we obtain a direct relation between the independent variables immigration, employment rate, productivity and the dependent variable per capita income.